Analysis of competitive forces for cocoa farmers in San José de Cúcuta, Colombia - Otero-Gómez, Miller Eduardo (2024)
Introduction. Competitiveness measures the ability of a company or organization to produce and market a good or product more efficiently and effectively compared to other competitors. Objective. To analyze the competitive forces related to the productivity and marketing of cocoa beans by the cocoa farmers of San José de Cúcuta, and to provide information for future research aimed at improving the cocoa sector. Materials and Methods. The research was carried out in the municipality of San José de Cúcuta, in the rural areas of Guaramito, Matecaña, La Floresta, Banco de Arena, and Palmarito, Colombia, during 2022. The study population consisted of cocoa producers residing in the rural area of the municipality. The sampling was non probabilistic, representing a convenience sample, with 86 cocoa producers identified as willing to respond to the survey. The study was observational and quantitative in nature. Descriptive and inferential statistical methods were applied for data analysis. Results. Regarding the producers’ bargaining power over grain prices, 34.88 % considered it to be very low. In terms of access to cultivation technology, 47.67 % expressed it as low. Concerning production costs, 45.35 % reported them as high. As for substitute products, 84.88 % of the respondents perceived a medium to very high level threat. Conclusions. In the municipality of San José de Cúcuta, cocoa production is a significant productive and socio-economic activity. Regarding the power of marketers, cocoa farmers exert no positive influence over the prices of the grain produced in the study area; on the contrary, they are subjectted to the prices imposed by the country’s industries.